2015
DOI: 10.1080/13546783.2014.994035
|View full text |Cite
|
Sign up to set email alerts
|

Contraries as an effective strategy in geometrical problem solving

Abstract: A focused review of the literature on reasoning suggests that mechanisms based upon contraries are of fundamental importance in various abilities. At the same time, the importance of contraries in the human perceptual experience of space has been recently demonstrated in experimental studies. Solving geometry problems represents an interesting case as both reasoning abilities and the manipulation of perceptual–figural aspects are involved.\ud In this study we focus on perceptual changes in geometrical problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 78 publications
(63 reference statements)
1
27
0
Order By: Relevance
“…Our results from the explicit guidance condition add to the previous literature based on implicit guidance which we mentioned in the introduction (e.g., Gale and Ball, 2012; Branchini et al, 2015a). The participants in our study were exposed to a brief training session in which it was suggested that they approach the task by systematically transforming the spatial features of a problem into their contraries.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our results from the explicit guidance condition add to the previous literature based on implicit guidance which we mentioned in the introduction (e.g., Gale and Ball, 2012; Branchini et al, 2015a). The participants in our study were exposed to a brief training session in which it was suggested that they approach the task by systematically transforming the spatial features of a problem into their contraries.…”
Section: Discussionsupporting
confidence: 86%
“…It would also be interesting to explore new ways of stimulating both implicit processing (e.g., using dynamic visual tasks) and explicit processing (e.g., using different types of training). In terms of the current state of the art situation, only a provisional comparison can be made between the improvement due to prompting participants to use contraries in implicit and explicit guidance conditions based on the findings from the present study and that carried out by Branchini et al (2015a). There are obvious limits when one compares two experiments which do not perfectly coincide in terms of their experimental design.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations